(Same)‐sex in the city: Urbanisation and LGBTI rights expansion. (31st August 2020) - AYOUB, PHILLIP M.; KOLLMAN, KELLY
Abstract: Despite the notable successes of lesbian, gay, bisexual, transgender and intersex (LGBTI) activism in the region, individual European countries have varied considerably in the extent and speed with which they have adopted legislation to recognise the rights of their LGBTI citizens. Scholars have often turned to modernisation theory to explain these variable outcomes and argue that high levels of national wealth are an important factor in the success of LGBTI movements. Although the correlation between modernity, economic development and tolerance of LGBTI lifestyles is often treated as a truism in the literature, scholars have paid less attention to the precise mechanisms by which the complex processes associated with modernisation facilitate policy change. Drawing on the classic works of both modernisation theory and gay and lesbian history, we examine a less explored route by which modernisation leads to the expansion of LGBTI rights. Specifically, we posit that urbanisation facilitates the adoption of rights policies by strengthening LGBTI movements and enhancing their political effectiveness. To test this proposition, we use event history analysis and an original dataset that contains measures for institutional, cultural, economic and movement variables, as well as measures of urbanisation in 44 European countries between 1980 and 2015. Our findings support the contention that urbanisation has a strong effect on the formation of LGBTI movement organisations as well as the speed with which European states adopt both same‐sex union and anti‐discrimination legislation. The relationship between urbanisation and rights expansion persists even after controlling for a country's level of wealth, religious adherence and the influence of European institutions and norms.